Kesadaran Nasional Generasi Z: Menjaga Nasionalisme di Era Digital: Generation Z National Awareness: Maintaining Nationalism in the Digital Era - Merina, Merina; Djono, Djono (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
National consciousness is a vital element in shaping the identity and integrity of a nation. Amid the rapid flow of globalization and technological advancements, Generation Z, those born between the mid-1990s and early 2010s, faces unique challenges in upholding national values. This article aims to discuss the real challenges of national consciousness faced by Generation Z in the digital era, while also exploring their potential and opportunities to strengthen nationalism through relevant and contextual approaches. The methodology used in this research is a literature review, which involves collecting data and information from various sources, including academic articles and reference books. A descriptive analytical approach is applied to describe and present the gathered data without drawing definitive conclusions. Through both qualitative and quantitative approaches, this paper examines how Generation Z tends to be more open to global culture, yet still demonstrates a strong sense of patriotism, especially when confronted with issues concerning national sovereignty. However, their understanding of history, national ideology, and national symbols remains limited and in need of improvement. Therefore, an adaptive and creative approach is required, particularly through digital platforms and formal education, to instill national values that align with the unique characteristics of this generation.